Tactical Compromises: Authoritarian Survival Mechanisms of Sudan’s Inqaz Regime (1989-2019) - Abdelnabi, Dalia (AUC Knowledge Fountain, 2024)
How did the Inqaz regime survive a civil war, economic crises, mass upheavals, and political stagnation for thirty years? This question guides the study’s analysis of the survival of one of the MENA’s most resilient authoritarian regimes. Authoritarian durability is an adaptive risk-taking process of implementing politically costly plans to survive in power. This research investigates authoritarian survival through power-sharing reforms and coup-proofing tactics. The study highlights the role of the autocratic ruling coalition in maintaining regime durability and argues that intra-elite dynamics are key to understanding an autocrat’s exit without a clear successor. To this end, I investigate the changes in the ruling coalition's composition under the Inqaz regime across several periods punctuated by critical junctures and question the role of these changes in prolonging the regime's life. The guiding lens through which I tackle the regime’s resilience is the theory of coup-proofing. I complement the analysis with the political marketplace approach to better understand the last phases of the regime's cycle. The primary method of analysis is process tracing, connecting path-dependent events and finding their plausible causes, as adaptability-to-survive is a central focus. The study relies on secondary sources and over a dozen semi-structured interviews with Sudanese and non-Sudanese scholars and journalists. The study finds that the Inqaz regime survived in power through a series of elite reconfigurations and fell when its coup-proofing tactics backfired. In the end, the security elite triad came to the improbable yet tactical agreement that their survival hinges on the autocrat’s removal.